Beethoven's cello : five revolutionary sonatas and their world - Moskovitz, Marc; Todd, R. Larry (The Boydell Press, 2017)
"In 1796 the young Beethoven presented his first two cello sonatas at the court of Frederick William II, an avid cellist and the reigning Prussian monarch. Released in print the next year, these revolutionary sonatas forever altered the cello repertoire by fundamentally redefining the relationship between the cello and the piano and promoting their parity. Beethoven continued to develop the potential of the duo partnership in his three other cello sonatas - the lyrical and heroic Op. 69 and the two experimental sonatas Op. 102, No. 1 and No. 2, transcendent compositions conceived on the threshold of the composer's late style. In Beethoven's Cello, Marc D. Moskovitz and R. Larry Todd examine these seminal cornerstones of the cello repertoire and place them within their historical and cultural context. Also considered in a series of interludes are Beethoven's three variation sets, his cello-centric 'Triple' Concerto, and arrangements for cello and piano of other works. Two other interludes address the cellos owned by Beethoven and the changing nature of his pianos. Featuring a preface by renowned cellist Steven Isserlis and concluding with translated reviews of the composer's cello music published during his lifetime, Beethoven's Cello is the ideal companion for cellists, pianists, musicologists and chamber-music devotees desiring a comprehensive understanding of this beloved repertoire."--Jacket flap